Tradition in the Twenty-First Century : Locating the Role of the Past in the Present - Howard, Robert Glenn; Blank, Trevor J. (Book collections on Project MUSE., 2013)
In this book, eight diverse contributors explore the role of tradition in contemporary folkloristics. For more than a century, folklorists have been interested in locating sources of tradition and accounting for the conceptual boundaries of tradition, but in the modern era, expanded means of communication, research, and travel, along with globalized cultural and economic interdependence, have complicated these pursuits. Tradition is thoroughly embedded in both modern life and at the center of folklore studies, and a modern understanding of tradition cannot be fully realized without a thoughtful consideration of the past's role in shaping the present. Emphasizing how tradition adapts, survives, thrives, and either mutates or remains stable in the modern world, the contributors pay specific attention to how traditions now resist or expedite dissemination and adoption by individuals and communities. This complex and intimate portrayal of tradition in the twenty-first century offers a comprehensive overview of the folkloristic and popular conceptualizations of tradition from the past to present and presents a thoughtful assessment and projection of how "tradition" will fare in years to come.